Restoration of a Critical Mandibular Bone Defect Using Human Alveolar Bone-Derived Stem Cells and Porous Nano-HA/Collagen/PLA Scaffold - Xing Wang; Helin Xing; Guilan Zhang; Xia Wu; Xuan Zou; Lin Feng; Dongsheng Wang; Meng Li; Jing Zhao; Jianwei Du; Yan Lv; Lingling E; et al. (Stem Cells International)
Periodontal bone defects occur in a wide variety of clinical situations. Adult stem cell- and biomaterial-based bone tissue regeneration are a promising alternative to natural bone grafts. Recent evidence has demonstrated that two populations of adult bone marrow mesenchymal stromal cells (BMSCs) can be distinguished based on their embryonic origins. These BMSCs are not interchangeable, as bones preferentially heal using cells that share the same embryonic origin. However, the feasibility of tissue engineering using human craniofacial BMSCs was unclear. The goal of this study was to explore human craniofacial BMSC-based therapy for the treatment of localized mandibular defects using a standardized, minimally invasive procedure. The BMSCs’ identity was confirmed. Scanning electron microscopy, a cell proliferation assay, and supernatant detection indicated that the nHAC/PLA provided a suitable environment for aBMSCs. Real-time PCR and electrochemiluminescence immunoassays demonstrated that osteogenic markers were upregulated by osteogenic preinduction. Moreover, in a rabbit critical-size mandibular bone defect model, total bone formation in the nHAC/PLA + aBMSCs group was significantly higher than in the nHAC/PLA group but significantly lower than in the nHAC/PLA + preinduced aBMSCs. These findings demonstrate that this engineered bone is a valid alternative for the correction of mandibular bone defects.